2022
DOI: 10.3390/cancers14030720
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sarcopenia and Myosteatosis in Short- and Long-Term Outcomes Following Curative-Intent Surgery for Hepatocellular Carcinoma in a European Cohort

Abstract: Alterations of body composition, especially decreased muscle mass (sarcopenia) and impaired muscle quality (myosteatosis), are associated with inferior outcomes in various clinical conditions. The data of 100 consecutive patients who underwent partial hepatectomy for hepatocellular carcinoma (HCC) at a German university medical centre were retrospectively analysed (May 2008–December 2019). Myosteatosis and sarcopenia were evaluated using preoperative computed-tomography-based segmentation. We investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 55 publications
2
32
0
Order By: Relevance
“…2 The prevalence of pathological alterations of the SMC (e.g., sarcopenia or myosteatosis, sarcopenic obesity) has been reported to be ranging between 30 to 70% in liver transplant (LT) candidates and in patients with chronic liver disease (CLD). 3,4 Landmark studies have raised an increasing awareness to fight malnutrition, clinical frailty and improve physical fitness in patients awaiting or undergoing LT. [5][6][7][8][9][10] Even though observational cohort studies demonstrated a robust prognostic link between BC and poor clinical outcomes, many questions remain regarding: (I) the exact role of the SMC in outcomes (e.g., epiphenomenal sign of critical illness vs. aggravating factor); (II) the prognostic significance of persisting and progressing alterations of the SMC in clinical outcomes over time and following LT as well as (III) the therapeutic approaches. In addition, there is a large heterogeneity in published studies in terms of modalities, definitions and selection criteria to assess BC calling for further discussions and consensus on these.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The prevalence of pathological alterations of the SMC (e.g., sarcopenia or myosteatosis, sarcopenic obesity) has been reported to be ranging between 30 to 70% in liver transplant (LT) candidates and in patients with chronic liver disease (CLD). 3,4 Landmark studies have raised an increasing awareness to fight malnutrition, clinical frailty and improve physical fitness in patients awaiting or undergoing LT. [5][6][7][8][9][10] Even though observational cohort studies demonstrated a robust prognostic link between BC and poor clinical outcomes, many questions remain regarding: (I) the exact role of the SMC in outcomes (e.g., epiphenomenal sign of critical illness vs. aggravating factor); (II) the prognostic significance of persisting and progressing alterations of the SMC in clinical outcomes over time and following LT as well as (III) the therapeutic approaches. In addition, there is a large heterogeneity in published studies in terms of modalities, definitions and selection criteria to assess BC calling for further discussions and consensus on these.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of pathological alterations of the SMC (e.g., sarcopenia or myosteatosis, sarcopenic obesity) has been reported to be ranging between 30 to 70% in liver transplant (LT) candidates and in patients with chronic liver disease (CLD) 3,4 . Landmark studies have raised an increasing awareness to fight malnutrition, clinical frailty and improve physical fitness in patients awaiting or undergoing LT 5–10 …”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, impairment of BC, including depletion of muscle mass (sarcopenia) as well as muscle quality (myosteatosis) have been found to affect perioperative outcomes in various clinical conditions 3 5 . Previous studies have shown a strong association of sarcopenia with poor overall survival (OS) in patients undergoing liver resection for HCC 6 8 and recent studies conducted by our group detected not only a high prevalence of myosteatosis, but also an association between myosteatosis and poor perioperative outcomes in patients undergoing orthotopic liver transplantation (OLT) 9 , 10 . Reduced bone mineral density (BMD), defined as osteopenia, is the most important factor of bone fragility 11 .…”
Section: Introductionmentioning
confidence: 75%
“…In this study, we found a positive correlation between the SM-RA and serological indicators (HGB, albumin, Scr, and AST) in HCC patients, which indicated the nutritional status, organ function, and metabolic status of the body. Recent reports have also shown that skeletal muscle quality (myosteatosis), rather than quantity (sarcopenia), is an independent prognostic marker for a variety of tumorigenesis ( 15 , 23 ). Therefore, myosteatosis may be useful for quantitatively assessing a common clinical phenotype for the overall status of the body, such as metabolic status, gene status, obesity, inflammation and so on, which is thought to underlie variability in responses to immune-HAIC therapy and prognosis in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Myosteatosis is evaluated on the conventional computed tomography (CT) images, using the radiological characterization of skeletal muscle radiation attenuation (SM-RA) ( 12 14 ). A growing body of evidence suggests myosteatosis as the negative indicator of poor treatment response and prognosis in several cancers, including HCC ( 15 ). However, there is limited understanding of the clinical impact of assessing the baseline body composition, for example, CT-derived myosteatosis, in HCC patients undergoing immune-HAIC therapy.…”
Section: Introductionmentioning
confidence: 99%